Occurrence of Fungi and Mycotoxins in Fish Feeds and Their Impact on Fish Health - Esther Marijani; Emmanuel Kigadye; Sheila Okoth (International Journal of Microbiology)
The rapid population growth in developing countries has led to strong pressure on capture fisheries. However, capture fisheries have reached their maximal limits of fish production and are supplemented by farmed fish. The growth in aquaculture has led to high demand for fish feeds, which play a very important role in fish nutrition and health. Use of animal protein in fish feeds is expensive; hence, a majority of farmers from developing countries use local feed ingredients from plant origin as a source of dietary protein. However, these ingredients of plant origin provide the best natural substrates for fungi, which can be easily accompanied by mycotoxin development under suitable conditions. The locally made feed comprises ingredients such as soybeans, cottonseed cake, and wheat and maize bran which are mixed together and ground after which the compounded feed is pelleted and stored. Among the ingredients, maize and oilseeds are more susceptible for mycotoxigenic fungi compared to other ingredients. The outcomes of mycotoxin contamination in fish feeds are not different from other animal species intended for human consumption, and they are directly associated with production losses, particularly decreased weight gain and feed conversion, impaired immune system and reproductive performance, and increased fish mortality. Fish may also carry mycotoxin residues along the food chain, thus compromising human health. Hence, it is important to ensure the control of mycotoxin contamination in fish feeds, especially during the production and storage.